Dopaminergic signaling to ventral striatum neurons initiates sniffing behavior - Natalie L. Johnson; Anamaria Cotelo-Larrea; Lucas A. Stetzik; Umit M. Akkaya; Zihao Zhang; Marie A. Gadziola; Adrienn G. Varga; Minghong Ma; Daniel W. Wesson (Nature Communications)
Abstract Sniffing is a motivated behavior displayed by nearly all terrestrial vertebrates. While sniffing is associated with acquiring and processing odors, sniffing is also intertwined with affective and motivated states. The systems which influence the display of sniffing are unclear. Here, we report that dopamine release into the ventral striatum in mice is coupled with bouts of sniffing and that stimulation of dopaminergic terminals in these regions drives increases in respiratory rate to initiate sniffing whereas inhibition of these terminals reduces respiratory rate. Both the firing of individual neurons and the activity of post-synaptic D1 and D2 dopamine receptor-expressing neurons are coupled with sniffing and local antagonism of D1 and D2 receptors squelches sniffing. Together, these results support a model whereby sniffing can be initiated by dopamine’s actions upon ventral striatum neurons. The nature of sniffing being integral to both olfaction and motivated behaviors implicates this circuit in a wide array of functions.